Kinetics of central macular thickness reduction in patients with macular edema after intravitreal drug therapy - He L (Dove Medical Press, 2011)
Lingmin He, Annie Chan, Theodore Leng, Mark S BlumenkranzDepartment of Ophthalmology, Stanford University School of Medicine, Stanford, California, USABackground: The purpose of this study was to characterize central macular thickness and retinal volume following intravitreal injections using time domain and spectral domain optical coherence tomography (TD-OCT and SD-OCT, respectively).Methods: Nine patients with macular edema secondary to diabetes or retinal vein occlusion treated with intravitreal triamcinolone 4.0 mg and/or bevacizumab 1.25 mg were enrolled. Central macular thickness and volume was measured by SD-OCT and TD-OCT scan at baseline, and 1, 3, 6, 24, 48 hours, and 1 week postinjection.Results: Equations were derived to describe central macular thickness and volume reduction in the hours following intravitreal injection. Measurements of central macular thickness by SD-OCT were significantly reduced by 3 hours (P = 0.03) and retinal volume by 6 hours (P = 0.03). Central macular thickness measured 40.9 (28.6–53.2) µm thicker on the SD-OCT instrument while volume measured 3.47 (3.27–3.66) mm3 higher.Conclusion: Significant central macular thickness and volume reductions occur in the first hours after injection with triamcinolone and/or bevacizumab.Keywords: retinal vein occlusion, intravitreal injection, diabetic retinopathy